Äldre and Yngre Västgötalagen – some linguistic evidence - Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2009)
The article studies two of the oldest Swedish texts, the legal codices from the province of Västergötland, Äldre Västgötalagen (ÄVL), dated at 1225 and Yngre Västgötalagen (YVL), dated at ca 1280. The younger of the texts is a continuation of the older one and includes several additions. The texts are compared with particular respect to the nominal categories – the developing definiteness and the declining case. In particular, the definite forms are studied in much detail. The results confirm an earlier hypothesis that the younger text is based on a copy of the older one different from the one in our possession today. Also, it substantiates the claim that this missing original was more archaic than the one surviving today.